Ambiguity aversion: bibliometric analysis and literature review of the last 60~years - Christoph Bühren; Fabian Meier; Marco Pleßner (Management Review Quarterly, 2021)
We conduct a bibliometric analysis and review the literature of the last six decades on ambiguity aversion. Comparing trends in theoretical, experimental, and empirical contributions, our study presents the main aspects that are discussed in this literature. We show the increasing relevance of ambiguity aversion for decision-making research and discuss factors influencing attitudes on ambiguity. Our literature review reveals unsolved problems in the research on ambiguity and gives an outlook on new ventures for future research.
Keywords: 650; Ambiguity aversion; Bibliometric analysis; Literature review; Ellsberg paradox